Clarificação do extrato aquoso de Stevia Rebaudiana Bertoni através de adsorção em zeólitas modificadas - Moraes, Élida de Paula (2000)
The glicosydes, stevioside, rebaudioside A, B, C, D, E and dulcosides A and B, wichare extracted of the dry leaves of the native plant denominated Stevia rebaudiana Bertonior simply Stevia, are used as sweeteners. One of the process stages of extraction of thoseglicosides is the clarification of the aqueous extract of Stevia. The clarification is a very important stage because the visual quality of the product depends on it, for that reason there are many published works and research in progress in that area. The conventional processes of clarification has some disadvantages: it leaves toxic residues to the health, it has a high cost of implantation and maintenance, and the operational technology consumes reagentes and specialized labor which elevates cost. For this reason a simple technology that does not result in toxic residues in the final product is interesting and necessary. In the present work ionic exchanges were made with ions of calcium and barium in zeolites NaX and NaA. The effect of the contact of aqueous extract of dry leaves of Stevia rebaudiana Bertoni leaves with the CaX BaX, CaA and BaA was evaluated. The extract of Stevia that was in contact with the zeolite CaX showed the largest clarification and did not present alterations of its initial of characteristics, in terms of concentration of glicosydes and flavour. In batch tests at ambient temperature, the contact of Stevia aqueous extract and CaX zeolite provided a clarification between 70-80%, resulting in a decrease of approximately 10% CHT, the variation are not significant and of 30% Brix. Tests weremade varying the zeolite mass, to obtain the ideal mass of zeolite for the process. Similar tests were performed to evaluated the temperature effect in which the zeolite mass and the concentration of the extract were maintained constant. It was also observed that agitation is fundamental, because it decreases the process time. It was verified that the zeolite can be regenerated, allowing its use for than once; and with the regenerated zeolite, it was possible to obtain a clarification between 65-70%. After the performance on these batch tests, an experimental module consisting of a fixed bed of zeolite CaX was built. The Stevia aqueous extract was passed upwards and flow rate was controled to promote adequate contact. In the clarification of the Stevia aqueous extract, the process with zeolites has proven to be advantageous because: it has low cost (zeolite), it doesn't leave residues that can be toxic, the operational technology is of easy understanding and application and in addition, is not associated to risks to the environment.